2014
DOI: 10.1016/j.drudis.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

PI3K inhibitors as potential therapeutics for autoimmune disease

Abstract: Abstract:Aberrant over-activation of the immune system can give rise to chronic and persistent self-attack, culminating in autoimmune disease. This is currently managed therapeutically using potent immunosuppression and anti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…PI3K signaling has a complex role in regulation of the immune system and has been identified as a therapeutic target for autoimmune diseases. 10 In a model of rheumatoid arthritis, inflammatory cytokines induced PI3Kd mRNA in cultured synoviocytes, and the selective inhibition of PI3Kd diminished joint erosion in an animal model. 20,21 PI3Kd also has potential roles in the pathogenesis of systemic lupus erythematosus and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PI3K signaling has a complex role in regulation of the immune system and has been identified as a therapeutic target for autoimmune diseases. 10 In a model of rheumatoid arthritis, inflammatory cytokines induced PI3Kd mRNA in cultured synoviocytes, and the selective inhibition of PI3Kd diminished joint erosion in an animal model. 20,21 PI3Kd also has potential roles in the pathogenesis of systemic lupus erythematosus and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 PI3Kd also has potential roles in the pathogenesis of systemic lupus erythematosus and multiple sclerosis. 10 Likewise, studies have identified a role of the PI3K pathway in the pathogenesis of GO. The PI3K pathway is activated by either TSHR or IGF-1R stimulation in GO orbital fibroblasts, and its activation is correlated with hyaluronan production and adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,5 PI3Kδ is highly enriched in leukocytes, making it an attractive target for the treatment of inflammatory conditions, such as asthma 6 , chronic obstructive pulmonary disease 7 (COPD) and autoimmune diseases. 8 Furthermore, both PI3Kδ knock-out and kinase dead knock-in mice are viable and have a phenotype consistent with immunological effects on B-cells, T-cells and neutrophils. 9 PI3Kγ is also a reported target in inflammatory disease 10 and mutagenic mice are again viable, however PI3Kα and β knock-out mice are embryonically lethal, indicating the importance of subtype specific inhibitors for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 97%